The effect of kweni mango and randu honey addition on the characteristics of synbiotic etawa goat milk - SAMSUL RIZAL; A. S. SUHARYONO; SUSSI ASTUTI; AURA SABRINA DEWANTI; YEREMIA BAGUS NUGROHO (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Rizal S, Suharyono AS, Astuti S, Dewanti AS, Nugroho YB. 2024. The effect of kweni mango and randu honey addition on the characteristics of synbiotic etawa goat milk. Biodiversitas 25: 1580-1587. The addition of kweni mango and randu honey as ingredients for producing synbiotic etawa goat milk is widely known to have a significant effect on the characteristics of the product. Therefore, this study aimed to identify the best formulation of kweni mango and randu honey in producing synbiotic etawa goat milk. The experiment was conducted using a completely randomized block design with 4 replications. A single factor with six levels of formulations of kweni mango extract and randu honey was used in producing synbiotic etawa goat milk. These formulations included F1 (0%:25%), F2 (5%:20%), F3 (10%:15%), F4 (15%:10%), F5 (20%:5%), and F6 (25%:0%). Subsequently, the microbiological, chemical, and sensory properties, as well as antimicrobial activity of the product were evaluated. The data obtained were statistically analyzed using ANOVA and the Least Significant Difference (LSD) test at a 5% significance level. The results showed that formulation (F4) containing 15% kweni mango extract and 10% randu honey produced the best synbiotic Etawa goat milk beverage. In addition, F4 formulation showed higher antibacterial activity against Staphylococcus aureus than Escherichia coli. The optimal beverage met the standards for lactic fermentation products from a chemical perspective and was favored by the panelists.